PERAN MODEL PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN MINAT DAN MOTIVASI BELAJAR AL-QUR’AN TKA/TPA - Andi Hasrianti; Suharti, Suharti; Mardiana (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The Qur'an is the main source of Islamic teachings that must be introduced from an early age through effective and interesting learning. However, in practice, Qur'an learning in Al-Qur'an Kindergartens (TKA) and Al-Qur'an Education Parks (TPA) still use conventional models that tend to be monotonous, thus affecting the interest and motivation of students to learn. This community service activity aims to increase students' interest and motivation to learn the Qur'an through the application of interactive learning models at TKA/TPA Masjid H. Zainuddin Dg. Mabelo Mosque, introduce the interactive learning model as an effective learning model to TKA/TPA teachers as a strengthening of teaching capacity, support Al-Qur'an learning by involving the role of the community, and to facilitate the availability of Al-Qur'an learning facilities in the form of Al-Qur'an and Iqra for TKA/TPA students. The implementation method includes three main stages: planning, implementation, and evaluation with a participatory approach. Activities consisted of an introduction to the interactive learning model, a workshop on strengthening the capacity of teachers, demonstration of learning methods, and distribution of Al-Qur'an and Iqra. The results of the activities show that the interactive learning model can increase santri involvement, build a fun learning atmosphere, and encourage teachers to adopt more innovative approaches. The evaluation of the activities also showed a positive response from teachers, students, and the community. This activity is expected to be an example of good practice that can be replicated and developed sustainably in other Qur'anic education institutions.